The Influence of Advertising and Testimonials Against Online Shopping Purchasing Decision Followers in Kedaicemilanbabyblue Instagram - Yori Manis Tika; Lely Arrianie; Mas Agus Firmansyah; Levy Oktridarti (Journal of Social Science and Humanities, 2023)
This study aims to determine the effect of advertising and testimonials on the decision to purchase online shopping followers in kedaicemilanbabylue. In this study using AIDCA theory that explains the elements of attention, interest, desire, conviction, and action is used in the manufacture of ads and testimonials that affect the purchase decision followers to shop online on kedaicemilanbabyblue intagram. The method used is quantitative method. The results of the first hypothesis of this study is advertising significantly influence the decision with the percentage of the calculation of 79.3%. the second hypothesis states that the testimony significantly influence the purchase decision with a value of 63.2%. third hypothesis result is advertisement and testimony together influence to purchase decision with value 95.8%. thus there is 4.2% influence of other variables not examined in this study. The results of this study suggest that in influencing purchasing decisions online followers are more dominantly influenced by advertising than with testimony. This is in line with the thoughts in AIDCA theory which explains that ads formed with the elements of attetion, interest, desire, conviction and action will be able to attract potential customers in making purchasing decisions about a product offered in the ad